2012
DOI: 10.1007/s00442-011-2243-2
|View full text |Cite
|
Sign up to set email alerts
|

Testing the directed dispersal hypothesis: are native ant mounds (Formica sp.) favorable microhabitats for an invasive plant?

Abstract: Ant-mediated seed dispersal may be a form of directed dispersal if collected seeds are placed in a favorable microhabitat (e.g., in or near an ant nest) that increases plant establishment, growth, and/or reproduction relative to random locations. We investigated whether the native ant community interacts with invasive leafy spurge (Euphorbia esula) in a manner consistent with predictions of the directed dispersal hypothesis. Resident ants quickly located and dispersed 60% of experimentally offered E. esula see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Studies have reported that mound-type nests made from soil and/or litter have nutrient profiles that differ from those of surrounding soil or forest floor (Ohashi et al 2007a; Domisch et al 2008). Moreover, specific fauna and flora are found at ant mounds (Berg-Binder and Suarez 2012; Laakso and Setälä 1997). Similarly, subterranean ant nests can affect water infiltration rates (Lavelle and Spain 2003) and soil erosion (Cerdà and Jurgensen 2008) by decreasing soil bulk density and increasing soil porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that mound-type nests made from soil and/or litter have nutrient profiles that differ from those of surrounding soil or forest floor (Ohashi et al 2007a; Domisch et al 2008). Moreover, specific fauna and flora are found at ant mounds (Berg-Binder and Suarez 2012; Laakso and Setälä 1997). Similarly, subterranean ant nests can affect water infiltration rates (Lavelle and Spain 2003) and soil erosion (Cerdà and Jurgensen 2008) by decreasing soil bulk density and increasing soil porosity.…”
Section: Introductionmentioning
confidence: 99%
“…No parasitism of C. castaneus has been observed by us or reported in the literature, although protection against parasitism is often a function of leaf shelters (e.g., LoPresti and Morse 2013). Ants facilitate the abundance of nonnative plant species by providing establishment sites of reduced competition (Farji-Brener et al 2010, Berg-Binder andSuarez 2012), but just the opposite may be the case in our system if multiple species use the same shelters, increasing competition (Sliwinski and Sigmon 2013) or parasitism (Lill et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Understanding these positive effects of ecosystem engineers may help mitigate the spread and resultant impacts of invasive species (Bulleri et al 2008, Pearse andAltermatt 2013). Despite the prevalence of insects, there are only two published studies of native insect species (both ants) influencing the abundance of nonnative species (both nonnative plants) through ecosystem engineering (Farji-Brener et al 2010, Berg-Binder andSuarez 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several benefits gained by plants have been identified; namely, directed dispersal, distance dispersal, predator avoidance and fire avoidance (Giladi ; Warren & Giladi ), although the relative importance of these benefits varies among ecosystem types (Giladi ; Rico‐Gray & Oliveira ). The directed dispersal of seeds to ant nests can be beneficial when nests are enriched with nutrients (Davidson & Morton ; Beattie & Culver ), resulting in greater plant growth (Culver & Beattie ; Davidson & Morton ; Berg‐Binder & Suarez ) and survival compared with plants derived from undispersed seeds (Davidson & Morton ; Hanzawa et al . ).…”
Section: Introductionmentioning
confidence: 99%